EFEKTIVITAS PROGRAM KEMITRAAN PETERNAKAN SAPI DI KABUPATEN LAMPUNG SELATAN - Sri Handayani; Irmayani Noer (Universitas Galuh Ciamis, 2021)
The issue of feeder cattle import policy requires feedlots to carry out breeding which requires a long time. Limitations of cages and the risk of breeding business for feedlots, as well as limited capital and technology for cattle breeders are the basis for the partnership between feedlots and breeders. The purpose of this research are to analyze the effectiveness of the community cattle breeding partnership in South Lampung Regency. The research method that will be used is a survey method to be precise in the 2 biggest cattle breeding centers, namely Sidomulyo and Tanjungsari Districts, South Lampung Regencies. The effectiveness ratio uses a simple statistical method of comparison between the realization and the target. Furthermore, the effectiveness criteria refer to the Ministry of Home Affairs Research and Development. The results and discussion show that the implementation of the community cattle breeding partnership program in South Lampung Regency in terms of input is quite effective with an effectiveness ratio of 82.5%. In terms of process and output, the implementation of the partnership has been effectively carried out, namely 90.6% and 92%.